Optimization and characterization of bulk hexagonal boron nitride single crystals grown by the nickel-chromium flux method - Hoffman, Timothy B. (Kansas State University, 2016)
Hexagonal boron nitride (hBN) is a wide bandgap III-V semiconductor that has seen new interest due to the development of other III-V LED devices and the advent of graphene and other 2-D materials. For device applications, high quality, low defect density materials are needed. Several applications for hBN crystals are being investigated, including as a neutron detector and interference-less infrared-absorbing material. Isotopically enriched crystals were utilized for enhanced propagation of phonon modes. These applications exploit the unique physical, electronic and nanophotonics applications for bulk hBN crystals. In this study, bulk hBN crystals were grown by the flux method using a molten Ni-Cr solvent at high temperatures (1500°C) and atmospheric pressures. The effects of growth parameters, source materials, and gas environment on the crystals size, morphology and purity were established and controlled, and the reliability of the process was greatly improved. Single-crystal domains exceeding 1mm in width and 200μm in thickness were produced and transferred to handle substrates for analysis. Grain size dependence with respect to dwell temperature, cooling rate and cooling temperature were analyzed and modeled using response surface morphology. Most significantly, crystal grain width was predicted to increase linearly with dwell temperature, with single-crystal domains exceeding 2mm in at 1700°C. Isotopically enriched ¹⁰B and ¹¹B hBN crystal were produced using a Ni-Cr-B flux method, and their properties investigated. ¹⁰B concentration was evaluated using SIMS and correlated to the shift in the Raman peak of the E[subscript 2g] mode. Crystals with enrichment of 99% ¹⁰B and >99% ¹¹B were achieved, with corresponding Raman shift peaks at 1392.0 cm⁻¹ and 1356.6 cm⁻¹, respectively. Peak FWHM also decreased as isotopic enrichment approached 100%, with widths as low as 3.5 cm⁻¹ achieved, compared to 8.0 cm⁻¹ for natural abundance samples. Defect selective etching was performed using a molten NaOH-KOH etchant at 425°C-525°C, to quantify the quality of the crystals. Three etch pit shapes were identified and etch pit width was investigated as a function of temperature. Etch pit density and etch pit activation energy was estimated at 5×10⁷ cm⁻² and 60 kJ/mol, respectively. Screw and mixed-type dislocations were identified using diffraction-contrast TEM imaging.
Keywords: Crystal growth; Group III nitrides; Compound semiconductors; Materials science; Chemical engineering; Solution growth